Cloud a ward-based clinical pharmacist service improve patients' perception on medication information exchanged between healthcare professionals during hospitalization - Shanika, L.G.T.; Wijekoon, C.N.; Jayamanne, S.; Coombes, J.; Coombes, I.; De Silva, A.; Dawson, A. (My University, 2017)
Attached

Inadequate communication between healthcare professionals and patients during hospital stay is a global issue. The objective of this study was to assess the patients’ perception about ward-based clinical pharmacy service (CPS) on medication information exchanged between healthcare professionals and patients during their hospital stay. This was a part of non-randomized controlled clinical trial conducted in a tertiary care hospital in Sri Lanka involving in-patients with non-communicable chronic diseases. The control group (CG) received standard care. The intervention group (IG) received CPS in addition to the standard care. The CPS included a medication history, prospective medication review, making recommendations to the healthcare team and patients when drug-related problems were identified, and patient education about medicines at discharge. A structured interview was performed by telephone on the 6th day after discharge to identify patients perceptions regarding the medication information exchanged during the index hospital admission.

334 and 311 patients in the IG and CG respectively were contacted. Significantly larger percentage of patients in the IG recalled being asked about their pre-admission medications (IG=97%, CG=92%, P= 0.002) and past history of allergies (IG=91%, CG= 83%; P= 0.002). A significantly larger percentage of patients in CG reported that they did not receive adequate information about their medicines during hospitalization (CG=60.8%, IG=1.5%, P<0.001). Both IG (100%) and CG (97.7%) recalled that they received information on dose and frequency of medicine whereas the indication was explained to significantly small percentage of CG (IG = 98.2%, CG= 29.3%; P <0.001). A smaller proportion of intervention patients (IG – 1.8%, CG – 25%; P <0.001) had problems to clarify at discharge and of them 83.3 %(5/6) received a chance to discuss them prior to discharge. Only 9% of patients in the CG (7/78) received this opportunity (P<0.001).more than 90% (312/334) of patients in the IG reported that they received medicine related information from the ward pharmacist.

The study shows that the medication information exchange between patient and health care professionals was better in IG. Large majority of patients in the IG reported that the ward-based clinical pharmacist was their main drug information source. This study demonstrates the positive contribution of the ward-based clinical pharmacist as a medication information source.
Keywords: Clinical pharmacy service, Medication information, Hospitalization